Perceptions of Higher Education Students in South Africa towards Online Teaching and Learning during COVID-19 Pandemic - Ramotshwane, Malebye Wilson Plaatjie; Sam, Ntuli Thembelihle; Matshonisa, Seeletse Solly (Berkala Kedokteran, 2024)
This study evaluates how students view online teaching and learning during COVID- Pandemic. A cross-sectional descriptive survey of University of Technology (UT) students at the Ga-Rankuwa Campus was conducted. Data were gathered from 295 students using a self-administered questionnaire and analysed using descriptive statistics. Prior to the pandemic, 25.1% of the students used online learning platforms for at least six hours; however, during the pandemic, 53.6% of the students did so (p<0.001). Students said that learning online was interesting (54.9%) and fun (55.1%) and allowed them to ask questions (59.4%). About 62% found teachers to be well prepared for the lessons. Over half (56.5%) of the pupils thought they were ready for their careers. Benefits of online learning included not having to travel, saving money, allowing students to learn at their own pace, and increased comfort; drawbacks included the need for an internet connection, a lack of gadgets, and interruptions from family. Students find online learning to be convenient, efficient, entertaining, and engaging. The absence of electronics, erratic Internet connections, and family distractions were experienced.